2019
DOI: 10.1186/s12885-019-5541-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the potential clinical benefit of Selumetinib in resensitising advanced iodine refractory differentiated thyroid cancer to radioiodine therapy (SEL-I-METRY): protocol for a multicentre UK single arm phase II trial

Abstract: Background Thyroid cancer is the most common endocrine malignancy. Some advanced disease is, or becomes, resistant to radioactive iodine therapy (refractory disease); this holds poor prognosis of 10% 10-year overall survival. Whilst Sorafenib and Lenvatinib are now licenced for the treatment of progressive iodine refractory thyroid cancer, these treatments require continuing treatment and can be associated with significant toxicity. Evidence from a pilot study has demonstrated feasibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 26 publications
0
28
0
2
Order By: Relevance
“…Interestingly, these preliminary data suggest a particularly high efficacy of this therapeutic approach in NRAS -mutated tumors. Given these promising results, there are several ongoing clinical trials utilizing selumetinib as an adjunct to RAI therapy in larger patients populations ( Table 2 ) [ 127 ]. The second-generation MEK inhibitor trametinib is being evaluated in an ongoing phase II trial implementing pretreatment with trametinib, followed by 124I PET/CT-based lesional dosimetry and RAI therapy in patients with sufficiently restored RAI uptake ( identifier NCT02152995) ( Table 2 ).…”
Section: Targeted Therapies For Thyroid Cancermentioning
confidence: 99%
“…Interestingly, these preliminary data suggest a particularly high efficacy of this therapeutic approach in NRAS -mutated tumors. Given these promising results, there are several ongoing clinical trials utilizing selumetinib as an adjunct to RAI therapy in larger patients populations ( Table 2 ) [ 127 ]. The second-generation MEK inhibitor trametinib is being evaluated in an ongoing phase II trial implementing pretreatment with trametinib, followed by 124I PET/CT-based lesional dosimetry and RAI therapy in patients with sufficiently restored RAI uptake ( identifier NCT02152995) ( Table 2 ).…”
Section: Targeted Therapies For Thyroid Cancermentioning
confidence: 99%
“…Numerous small molecule compounds have been developed that target the MAPK pathway and based on the role of MAPK signaling in promoting EMP and stemness, inhibition of this pathway presents a logical therapeutic target. In line with this thought, emerging evidence indicates that selumetinib, a MEK1/2 inhibitor which has been used for phase I and II clinic trials in several kinds of malignant diseases (Bodoky et al, 2012;Hayes et al, 2012;Catalanotti et al, 2013;Ho et al, 2013;Jänne et al, 2013;Janne et al, 2015Janne et al, , 2016Carvajal et al, 2014Carvajal et al, , 2015Gupta et al, 2014;Brown et al, 2019), might be a novel therapeutic strategy for breast cancer. For example, Zolkiewska and colleagues found that selumetinib blocked EGF-induced expansion of CD44+/CD24-breast cancer stem cell associated populations (Wise and Zolkiewska, 2017).…”
Section: Targeting Of the Mapk Pathwaymentioning
confidence: 88%
“…Selumetinib, a MEK1/2 inhibitor, is under investigation in a multicenter, phase-II trial with promising results based on the pilot study performed by Ho et al where 12/20 (60%) participants increased radioiodine uptake, with 8/12 being able to receive RAI. 63% achieved partial responses and 37% stable disease as best radiological response [153,154].…”
Section: Radioactive Iodine Resensitization/redifferentiationmentioning
confidence: 98%